Hak Waris Atas Tanah Adat Berdasarkan Hukum Waris Adat - Sopaliu, Marzan; Laturette, Adonia Ivonne; Lakburlawal, Mahrita Aprilya (BAMETI Customary Law Review, 2025)
Inheritance law is the law that regulates the transfer and continuation of tangible and intangible property from one generation to the next. The initiation of this procedure occurs throughout the lifetime of the parents. The subjects involved in inheritance distribution are the deceased (testator) and the heirs. The deceased and the heirs have a close relationship due to familial ties. This research aims to examine the inheritance rights over customary land based on customary inheritance law and to understand and explain it. The research uses normative juridical legal research, with primary and secondary legal materials as legal sources. The results of the study show that customary inheritance law is a law that is recognized and respected in its implementation, but the registration of inheritance transfers of land based on customary inheritance law cannot be fully carried out. The position of heirs in the inheritance distribution in Hila Village is passed down only to male children, while female children only have the right to enjoy the land, such as through farming, but are not considered heirs as long as there are male children.